Measuring head acceleration like a CHAMP - Arbogast, K. B.; Funk, J. R.; Solomon, J.; Crandall, J. (Journal of Athletic Training, 2023)
Keen interest has arisen in developing data-driven strategies to mitigate head injury and reduce repetitive head impacts in sports owing to concerns about the potential short-term and long-term neurologic consequences of these loads on the brain. Interventions can include advancements in equipment design, modifications to the rules of the game and training regimens, and enhancements to clinical assessments after an athlete sustains a concussive impact. One key to driving these improvements in athlete safety is the quantitative biomechanical measurement of head impact kinematics. Over the past 2 decades, technological advances in head kinematic measurement devices have made implementation more feasible, and as a result, these devices are sold commercially and used regularly across a range of scientific disciplines, including athletic training, exercise and sport science, physical therapy, neuroscience, and biomechanics. In addition, the price point of such devices has been reduced such that they are marketed to and used by parents and teams under the auspices of monitoring and protecting their athletes. The authors of a recent systematic review highlighted the exponential increase in peer-reviewed publications using such technology to quantify head loading in athletes and correlate kinematic measures with relevant clinical, physiological, and neuropsychological outcomes.